2016
DOI: 10.1016/j.jmb.2015.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Specialized Ribosomes: The Brussels Lecture

Abstract: “Specialized ribosomes” is a topic of intense debate and research whose provenance can be traced to the earliest days of molecular biology. Here, the history of this idea is reviewed, and critical literature in which the specialized ribosomes have come to be presently defined is discussed. An argument supporting the evolution of a variety of ribosomes with specialized functions as a consequence of selective pressures acting on a near-infinite set of possible ribosomes is presented, leading to a discussion of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
94
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 78 publications
(64 reference statements)
2
94
0
2
Order By: Relevance
“…However, these findings raise additional questions regarding the role for such regulation. Recent studies suggest that heterogeneity in the translational machinery, such as that observed for ribosomal proteins, may influence cell type- or developmental stage-specific translation (reviewed in Dinman, 2016; Xue and Barna, 2012). In addition, growing evidence indicates that many components of the translational machinery, including tRNA synthetases and tRNAs themselves, have a wide range of cellular functions (reviewed in Guo and Schimmel, 2013; Schimmel, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, these findings raise additional questions regarding the role for such regulation. Recent studies suggest that heterogeneity in the translational machinery, such as that observed for ribosomal proteins, may influence cell type- or developmental stage-specific translation (reviewed in Dinman, 2016; Xue and Barna, 2012). In addition, growing evidence indicates that many components of the translational machinery, including tRNA synthetases and tRNAs themselves, have a wide range of cellular functions (reviewed in Guo and Schimmel, 2013; Schimmel, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, an emerging body of research suggests that this is not the case. In particular, the diverse tissue specific phenotypes observed in human ribosomopathies and animal models point to an intriguing variation in requirements for ribosome biogenesis factors and/or ribosome biology during development [1, 4, 6, 7, 16, 25, 32, 36, 42, 46, 47, 50]. Here, we examined the developmental expression patterns of 13 ribosome-associated genes in Xenopus .…”
Section: Discussionmentioning
confidence: 99%
“…Several ribosome biogenesis factors and proteins have extra-ribosomal functions [16, 19, 44, 48, 6163], or roles in selective translation of internal ribosome entry site mRNAs [16, 43, 46, 47, 64], which may also contribute to ribosomopathy phenotypes. “Specialized ribosomes”, tailored to preferentially translate specific mRNAs, or to have specific properties in particular environments are another possibility [6, 16, 17, 25, 46, 47, 50]. Support for this is found primarily in observations that ribosomal gene expression levels do vary between tissues [6, 7, 49, 51, 65, 66], and direct evidence of a regulatory role for individual RP proteins in selective mRNA translation and embryonic tissue patterning [6, 16, 43, 49, 50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction of Rpl38/eL38 in a mouse model revealed that it does not affect global translational regulation but is selectively required for the translation of specific Hox genes that control patterning of the mammalian body plan through cis -regulatory elements residing in their 5′ untranslated regions (UTRs) [9,10•]. Emerging studies that highlight the functional significance of different RPs serving specific roles are reviewed elsewhere [11,12] and they suggest that the ribosome is not merely a static machine, but rather a dynamic one whose intrinsic components can be regulated and diversified to promote intricate regulation of translation.…”
mentioning
confidence: 99%